Sacred dread : Raïssa Maritain, the allure of suffering, and the French Catholic revival (1905-1944) - Moore, Brenna (University of Notre Dame Press, 2013)
In early twentieth-century France, a vast network of artists, writers, and religious seekers were drawn to Roman Catholicism's elaborate panoply of symbols centered on suffering. A preoccupation with affliction dominated the movement now known as the French Catholic revival, or the renouveau catholique - a movement considered a watershed in the history of the modern Catholic Church and the "golden age" of French Catholicism. In this book, the author examines the life and writings of Raïssa Maritain (1883-1960), one of the few women to contribute to this intellectual movement. The author explores the reasons why Maritain, a nonpracticing Jew, was attracted to this suffering-centered theological imagination and how she and other advocates transformed it in the wake of the Holocaust. This book offers readers a new understanding of a radical Catholic piety that was embraced by a wide range of pre-war intellectuals.